Loading presentation...

Present Remotely

Send the link below via email or IM

Copy

Present to your audience

Start remote presentation

  • Invited audience members will follow you as you navigate and present
  • People invited to a presentation do not need a Prezi account
  • This link expires 10 minutes after you close the presentation
  • A maximum of 30 users can follow your presentation
  • Learn more about this feature in our knowledge base article

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

DeleteCancel

Make your likes visible on Facebook?

Connect your Facebook account to Prezi and let your likes appear on your timeline.
You can change this under Settings & Account at any time.

No, thanks

6°____Kevin,Zihao

Exponential and logarithmic functions
by

kevin zhang

on 13 May 2013

Comments (0)

Please log in to add your comment.

Report abuse

Transcript of 6°____Kevin,Zihao

Zihao Li
Kevin Zhang
6 period Introduction Kevin Zhang Key Words Video Time Example 1
Solving for base is same Example 2 Example 3
Exponentiate each side using base Example 4
Use logarithm Example 5 Zihao Li Brother Log Product Property Quotient Property Power Property Inverse rule of logs Inverse rule of
exponentials Property of equality Solve for x Dropping the base Property of equality Solve for x Inverse rule of
exponential Solve for x Take logarithm Inverse rule of logs Quotient Property Solve for x Solve for extraneous solution Product Property Inverse rule of exponential Subtract both side by 36 Solve for x Check for solution -9 3 -36 -12 3x -12x -36 x 3 x -12 x 2 log (2x-6)=log (6x+7) 5 5 2x-6=6x+7 -4x=13 4x=-13 x=- _ 13 4 27 =9 x 2x+3 3 =3 3x 2(2x+3) 3x=4x+6 -x=6 x=-6 log (5x-3)=2 7 7 =7 2 log (5x-3) 7 5x-3=49 5x=52 x= _ 52 5 3 =28 x log 3 =log 28 3 3 x=log 28 3 x= _ log28 log3 x=3.033 x log x+log (x-9)=2 6 6 log (x -9x)=2 6 2 6 =6 log (x -9x) 6 2 2 x -9x=36 2 x -9x-36=0 2 (x-12)(x+3)=0 x=-3 or 12 log (-3) and log (-3-9) are not defined, 12 is the solution. 6 6 log mn=log m+log n b b log =log m-log n _ m n b b log m =n(log m) b n b log b =x b x b =x log x b Math Time Exponential and Logarithmic Functions END
Full transcript